Interactive solat multimedia courseware (i-Solat) / Nor Azila Awang Abu Bakar ... [et al.] - Awang Abu Bakar, Nor Azila; Mohamad Nor, Mohamad Imadi; Zainal Abidin, Nazatul Azleen; Mohamed, Zamzulani (2014)
This paper aims to highlight the development of a multimedia courseware to serve as a reference tool for people to get information regarding solat. From a preliminary survey conducted, it was found that existing solat courseware do not give detailed explanations on how to perform solat in a correct way where most of these courseware do not provide comprehensive contents. Interactive Solat Multimedia Courseware (i-Solat) is presented to help people to have better understanding about solat. In addition, the i-Solat Courseware is accompanied with facts from the science perspective on how solat movements can benefit our body. i-Solat covers comprehensive contents from performing ablution to reciting the doa. It is developed based on ADDIE Model which comprises of Analysis, Design, Development, Implementation and Evaluation phases. Another two phases are added which are Preliminary Study and Documentation to complete the project. The evaluation of the i-Solat Courseware was conducted on 30 respondents and to two Subject Matter Experts (SME). Questionnaire was used as an instrument to collect data. The results from the analysis indicate that the courseware had satisfied the respondents in terms of user interface, usability and content of the courseware.